ELECTRONIC INVOICING - Pavlāns, Vitālijs; Purviņš, Eduards; Ežmale, Sandra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The aim of the article is to explore the specificity of electronic billing in the Republic of Latvia and other countries of the European Union, to compare it, establish the issues related to the use of electronic bills as well as elaborate suggestions to prevent them. As a result of the work the authors elaborated suggestions for a conception of electronic bills, analysed the advantages and potential benefits of the offered conception.